ANALISIS SHIFT-SHARE DINAMIK PADA PEREKONOMIAN KOTA YOGYAKARTA - Gravitiani, Evi (Jurnal Ekonomi & Studi Pembangunan, 2006)
This paper attempts to analyze the economy of Yogyakarta by dynamic shift share method. The result shows that there is an increasing of economic growth of Yogyakarta before and after regional autonomy. There is a positive change in competitive advantage of Yogyakarta and positive change in output growth of Yogyakarta.